1980
DOI: 10.1042/bj1860799
|View full text |Cite
|
Sign up to set email alerts
|

Development of NADPH-producing pathways in rat heart

Abstract: The behaviours of the principal NADPH-producing enzymes (glucose 6-phosphate dehydrogenase, 6-phosphogluconate dehydrogenase, cytoplasmic and mitochondrial 'malic' enzyme and NAPD+-dependent isocitrate dehydrogenase) were studied during the development of rat heart and compared with those in brain and liver. 1. The enzymes belonging to the pentose phosphate pathway exhibit lower activities in heart than in other tissues throughout development. 2. The pattern of induction of heart cytoplasmic and mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 17 publications
2
26
0
Order By: Relevance
“…12 This conclusion was based largely on reports of increased myocardial levels of NADP ϩ -dependent isocitrate dehydrogenase (ICD)-an alternative enzyme capable of NADPH generation-resulting in a lower G6PD to ICD activity ratio in the heart relative to other tissues. 12 Importantly, however, these measurements do not distinguish between mitochondrial and cytosolic G6PD and ICD activities. In fact, ICD is likely a key generator of mitochondrial, rather than cytosolic, NADPH, particularly given that the vast majority of ICD and its required substrate, isocitrate, are localized to the mitochondria.…”
Section: G6pd and Cardiomyocyte Redox Statementioning
confidence: 99%
See 1 more Smart Citation
“…12 This conclusion was based largely on reports of increased myocardial levels of NADP ϩ -dependent isocitrate dehydrogenase (ICD)-an alternative enzyme capable of NADPH generation-resulting in a lower G6PD to ICD activity ratio in the heart relative to other tissues. 12 Importantly, however, these measurements do not distinguish between mitochondrial and cytosolic G6PD and ICD activities. In fact, ICD is likely a key generator of mitochondrial, rather than cytosolic, NADPH, particularly given that the vast majority of ICD and its required substrate, isocitrate, are localized to the mitochondria.…”
Section: G6pd and Cardiomyocyte Redox Statementioning
confidence: 99%
“…9,10 The role of G6PD in cardiomyocytes, however, remains highly controversial, 11 largely owing to the high myocardial concentration of NADP ϩ -dependent ICD, an alternative enzyme capable of NADPH generation. 12 This ICD pool, however, remains confined to the mitochondria and, thus, has little if any effect on cytosolic redox state. In this article, we demonstrate that G6PD is a critical cytosolic antioxidant enzyme in adult cardiomyocytes.…”
mentioning
confidence: 99%
“…In heart mitochondria, however, both transhydrogenase [94] and NADP-linked isocitrate dehydrogenase activities are much greater than in liver mitochondria. And& et al [95] have shown that for the latter enzyme this difference develops after birth, and propose that its main function in adult heart is to provide a pathway for isocitrate oxidation under oxygen deficiency.…”
Section: Relative Activities Of Nadp-and Nad-linked Isocitrate Dehydrmentioning
confidence: 99%
“…An isoform of NADP ϩ isocitrate dehydrogenase present in both the cytosol and mitochondria can also produce NADPH. 37 Recent studies suggest that the inner mitochondrial membrane NADPH transhydrogenase may also play a key role in the regulation of cellular NADPH content. 38 NADPH serves a number of essential cellular functions, including (1) de novo fatty acid synthesis, whereby it acts as a cofactor for both ␤-ketoacyl acyl carrier protein (ACP) reductase and enoyl ACP reductase, (2) the regulation of oxidative stress, where it acts as a cofactor for both glutathione reductase and thioredoxin reductase, producing reduced glutathione and reduced thioredoxin to deal with oxidative stress induced by toxins such as hydrogen peroxide, and (3) cholesterol biosynthesis, where it acts as a cofactor for 3-hydroxy-3-methylglutaryl CoA reductase, the rate-limiting enzyme of the mevalonate pathway.…”
Section: /Nadph Regulation Of Intermediary Energy Substrate Metabolismmentioning
confidence: 99%
“…As the heart does not synthesize significant amounts of fatty acids, 44 key lipogenic enzymes (including both G6P dehydrogenase and 6-phosphogluconate dehydrogenase of the PPP, the 265-kDa isoform of acetyl CoA carboxylase, and ATP citrate lyase) have minimal expression/activity in myocardial tissue. 37,45,46 The irreversible oxidative phase of the PPP, which serves as the primary pathway for producing NADPH for subsequent lipogenesis in tissues such as the liver and kidney, has extremely low metabolic rates in myocardial tissue, [47][48][49][50] due in part to low activity of G6P dehydrogenase, the rate-limiting enzyme of the oxidative portion of the PPP. 51,52 In addition, the NADPH required for alleviating oxidative stress via glutathione reductase has been shown to arise from NADP ϩ isocitrate dehydrogenase, as opposed to the dehydrogenase enzymes of the PPP.…”
Section: Ppp In the Heartmentioning
confidence: 99%